Hiding Files in Image Files Using the Steganography Method - Dedi Irawan (JSAI (Journal Scientific and Applied Informatics), 2020)
The need for communication in the digital era at this time makes the insertion of information applicable to digital files / media such as images, video, audio and text. Steganography inserts a secret message in a file / media without anyone realizing that the media has a secret message. Steganography (information hiding) is a technique to hide secret messages on a media host or also called a media cover. Steganography comes from Greek which means "hidden writing". Used in various forms for thousands of years. Steganography method is a method that inserts information into other data without destroying the data. Of course, using this steganography will not arouse the suspicion of other parties who are not entitled to receive information.